DESIGN DEVELOPMENT OF THE WATER SUPPLY WELLS AND METHODS OF THEIR CAPITAL REPAIR - V. V. Ivashechkin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents analysis of shortcomings and benefits of individual techniques for the capital repair of out-of-commission water wells of standard designs. The author considers the capital repair procedure of water well No 3B of Zhodino ‘Severniy’ water supply point by means of installing a repair filter of smaller diameter inside the failed one, cushioning the tubular annulus with gravel. It is shown that this kind of repair can be considered a temporary arrangement inasmuch as the water well specific yield and service life period will reduce significantly. For prolongation of the useful life of the water wells, the paper suggests performing preliminary unloading of their filters. The study reveals that the well capital repair by means of extracting the old filter and exchanging it with a new one can be complicated by the column burst along the welding joints working in tension. The performed column strength test demonstrated the fact that the required heave might exceed the welding joint tolerant tensile force owing to considerable friction of the column against the ground. The author arrives at a design equation of the heave required for extracting the production column with the filter applying only the static force. In which they offer to determine frictional force of the mudded filter against the formation from calculating formulae of the supporting power of an augered pile working with pulling loads. For decreasing the heaves via reducing frictional loads of the mudded filter against the formation, an improved design of the water well has been introduced recognized as an invention with the filter capable of downward biasing. Such water well design allows at the filter mud fill in the first instance the entire filtering column to be biased (knocked) down inside a special sleeve placed lower the settler by applying external buffing force, and then only extracting the filtering column out of the well by decreased traction pull. The energy balance equation for vertical displacement of the water well pipe column results in the computation expression for the hammer striking part weight and its drop height during the capital repair of the water well of improved design.